Incorporating Linguistic Landscape into Teaching: A Project-Based Learning for Language Practices at Primary School - Padmadewi, Ni Nyoman; Suarcaya, Putu; Artini, Luh Putu; Munir, Ahmad; Friska, Junita; Husein, Rahmad; Paragae, IGAPNS (International Journal of Elementary Education, 2023)
Project-based learning (PjBL) has been widely implemented in language learning. However, no research has been conducted on its use with linguistic landscape (LL) as a pedagogical tool in primary schools. This study was therefore conducted to look into the use of PjBL with LL for language practices and values in primary school. The purpose is to analyse the kinds of PjBL incorporating LL conducted, the teaching procedures implemented, the competencies and values promoted, and teachers’ opinions about its use for primary school. The study used a mixed-methods design that relied heavily on qualitative description and was supplemented with quantitative analysis. The study was conducted at a primary school, which was selected using the purposive sampling technique. Six teachers, six experts and students of grades 4, 5, and 6 teachers were involved. The amount of 520 LL was collected during the year 2022 using direct observation, questionnaire, interviews, and document study analysis. The data were analyzed qualitatively and quantitatively. The results show that PjBL of various kinds (PLS projects, legacy students’ projects, event-based and annual projects) has been incorporated into LL for language instruction. The teacher needs to prepare, introduce the concept of LL, allow students to observe and analyze the tasks, have discussions, design and creation, presentation and display, and reflection as the teaching procedure.  Multifaceted competence and values are promoted. The teachers and experts have positive opinions about it. The study implied that PjBL with LL is very beneficial for language practices and character values.